The Bedlam stacks - Pulley, Natasha (Bloomsbury, 2017)
In 1859, ex-East India Company smuggler Merrick Tremayne is trapped at home in Cornwall after sustaining an injury that almost cost him his leg. On the sprawling, crumbling grounds of the old house, something is wrong; a statue moves, his grandfather's pines explode, and his brother accuses him of madness. When the India Office recruits Merrick for an expedition to fetch quinine--essential for the treatment of malaria--from deep within Peru, he knows it's a terrible idea. Nearly every able-bodied expeditionary who's made the attempt has died, and he can barely walk. But Merrick is desperate to escape everything at home, so he sets off, against his better judgment, for a tiny mission colony on the edge of the Amazon where a salt line on the ground separates town from forest. Anyone who crosses is killed by something that watches from the trees, but somewhere beyond the salt are the quinine woods, and the way around is blocked. Surrounded by local stories of lost time, cursed woods, and living rock, Merrick must separate truth from fairytale and find out what befell the last expeditions; why the villagers are forbidden to go into the forest; and what is happening to Raphael, the young priest who seems to have known Merrick's grandfather, who visited Peru many decades before. The Bedlam Stacks is the story of a profound friendship that grows in a place that seems just this side of magical.